2016
DOI: 10.1016/j.radonc.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Lung stereotactic body radiotherapy with an MR-linac – Quantifying the impact of the magnetic field and real-time tumor tracking

Abstract: Background and purposeThere are concerns that radiotherapy doses delivered in a magnetic field might be distorted due to the Lorentz force deflecting secondary electrons. This study investigates this effect on lung stereotactic body radiotherapy (SBRT) treatments, conducted either with or without multileaf collimator (MLC) tumor tracking.Material and methodsLung SBRT treatments with an MR-linac were simulated for nine patients. Two different treatment techniques were compared: conventional, non-tracked deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 31 publications
5
101
0
Order By: Relevance
“…For our cohort, the average MLD presented was estimated to be above this 4 Gy cut-off value with ITV-based planning, and was lowered below 4 Gy with MLC tracking (3.5 Gy). A recent study simulated the effect of MLC tracking during MR-LINAC treatment and showed a mean lung dose reduction of 0.3 Gy, against our study with 0.8 Gy [33].…”
Section: Dose Reconstruction Limitationssupporting
confidence: 39%
“…For our cohort, the average MLD presented was estimated to be above this 4 Gy cut-off value with ITV-based planning, and was lowered below 4 Gy with MLC tracking (3.5 Gy). A recent study simulated the effect of MLC tracking during MR-LINAC treatment and showed a mean lung dose reduction of 0.3 Gy, against our study with 0.8 Gy [33].…”
Section: Dose Reconstruction Limitationssupporting
confidence: 39%
“…The impact of the magnetic field on electron trajectories, and consequently on dose distributions,, has been well established. A magnetic field orthogonal to the incoming radiation beam induces several effects on the dose distribution , , . One of these is the electron return effect (ERE), which occurs in regions of sharp density changes and is responsible for an increase in the interface surface dose.…”
Section: Introductionmentioning
confidence: 99%
“…A magnetic field orthogonal to the incoming radiation beam induces several effects on the dose distribution. 11,12,13 One of these is the electron return effect (ERE), which occurs in regions of sharp density changes and is responsible for an increase in the interface surface dose. Further effects include a dose shift, toward the direction perpendicular to both the beam and magnetic field, and an increase in the maximum dose deposition, due to the electron energy being deposited closer to the point of photon interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that centroid MLC tracking compensates for rigid target shifts, we have created treatment plans for a tracking scenario using the moving target volume (MTV) approach, which was utilized in Menten et al 30 Figure 4 schematically shows how construction of the MTV can be compared to the construction of the conventional ITV. Both methods rely on the GTV being delineated on each individual 4DCT phase.…”
Section: Methodsmentioning
confidence: 99%